MP32: The Pulmonary Embolism Severity Index (PESI) score and disposition decisions in Calgary emergency departments. (15th May 2017) - Brunet, S.; Wang, D.; Lang, E.
Abstract : Introduction: The Pulmonary Embolism Severity Index (PESI) score predicts short-term mortality from pulmonary embolism and low-risk patients suitable for home therapy. However, it is unknown if it is a driver for disposition decisions for emergency department (ED) patients. The primary objective of this study was to define the relationship between disposition decisions and the PESI score in Calgary zone hospitals.Methods: The PESI score was calculated retrospectively for 576 patients presenting to one of four Calgary zone hospitals for pulmonary embolism over the last 2 years. The calculated PESI score allowed the mortality risk of each patient to be estimated for very low risk (Class I, 0-1.6% 30-day mortality rate), low risk (Class II, 1.7-3.5% 30-day mortality rate), intermediate risk (Class III, 3.2-7.1% 30-day mortality rate), high risk (Class IV, 4.0-11.4% 30-day mortality rate), and very high risk (Class V, 10.0- 24.5% 30- day mortality rate). The patients were grouped based on being admitted to the hospital for inpatient care, or discharged for outpatient care. Descriptive statistics were used to describe the data.Results: Of the 576 patients, 317 (55%) were discharged and 259 (45%) were admitted to the hospital for inpatient care. Among admitted patients, 20.5% were considered Class I, 29.3% were Class II, 24.3% were Class III, 17.6% were Class IV, and 8.1% were Class V. Among discharged patients, 53.9 % were Class I, 25.6% were Class II, 15.5% were Class III, 4.4% were Class IV, and 0.6% were Class V. Of the 25 very high-risk (Class V) patients, 2 (8.0%) were discharged from the ED and treated as outpatients. Of the 223 very low risk (Class I) patients, 171 (76.7%) were discharged and 52 (23.3%) were admitted to hospital.Conclusion: A significant percentage of pulmonary embolism patients admitted to Calgary Zone hospital wards are PESI low risk (29.3%) or very low risk (20.5%). Implementation of a PESI score-based disposition pathway could improve the safety, cost-effectiveness and quality of ED disposition decisions for PE.